Analysis of the Effectiveness of the Management of the Regional Revenue and Expenditure Budget (APBD) of West Sulawesi Province for the Year 2020–2024: Analisis Efektivitas Pengelolaan Anggaran Pendapatan dan Belanja Daerah (APBD) Provinsi Sulawesi Barat Tahun 2020–2024 - Rezky Ramadhani; Dirmansyah Darwin; Arif Rahman Hasdik (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
This research analyzes the effectiveness of the management of the Regional Revenue and Expenditure Budget (APBD) of West Sulawesi Province during the 2020–2024 period. Effectiveness is measured using the ratio of expenditure realization to budget allocation as the main indicator. The data used is secondary data from the Budget Realization Report and official regional government documents. The analysis results show that the APBD management was very effective in 2020, 2022, and 2023, with effectiveness ratios above 94%. The year 2021 became an anomaly with a low effectiveness rate (48.54%) due to the impact of the COVID-19 pandemic and the earthquake. The year 2024 shows a realistic fiscal projection with the potential for a surplus. These findings emphasize the importance of accurate budget planning, the readiness of SKPD (regional work units) for implementation, and fiscal risk mitigation. It is recommended to improve the quality of regional spending, optimize Local Revenue (PAD), and strengthen public transparency to support sustainable and accountable development in West Sulawesi.